The effect of polystyrene foam in different doses on the blood parameters and relative mass of internal organs of white mice - Bilan, Maryna; Bilan, M. V.; Bilan, M.; Білан, Марина Володимирівна; Lieshchova, M. O.; Lieshchova, M. А.; Lieshchova, M.; Lieshchova, Maryna; Lieshchova, Marina; Leshchova, M. O.; Lieshova, M.; Лєщова, Марина Олексіївна; et al. (Oles Honchar Dnipropetrovsk National University, 2022)
Due to their durability, versatility and economy, plastic products are widely used in all spheres of human life. Despite the inertness of polymers, recent studiesshow the ability of microplastic to overcome natural tissue barriers, accumulate in the animal’s body, affect metabolism and change the intestinal microbiota, negatively affecting it. In a 42-day experiment, changes in the internal organs’ relative mass, blood biochemical and morphological parameters of white mice were established under the influence of different doses of polystyrene foam in their diet. Four groups of white mice consumed crushed polystyrene foam particles (10%, 1% and 0.1% by weight of the feed, control group without the addition of polystyrene foam). At the end of the experiment, the morphofunctional state of the internal organs was determined by the organ mass index and blood biochemical parameters. Adding crushed polystyrene foam to the feed in an amount of 1% causes a significant decrease in the mass index of the heart and stomach, 10% – only the heart, and 0.1% – does not affect this indicator. Polystyrene foam had a significant effect on blood biochemical parameters, regardless of the dose, causing an increase in the activity of aspartate aminotransferase against the background of a decrease in the activity of alkaline phosphatase. The content of total bilirubin, urea, urea nitrogen and cholesterol decreased, and the concentration of creatinine and total protein increased (due to the albumin fraction). The use of crushed polystyrene foam in mice did not cause significant changes in the blood morphological composition, except for a dose-dependent increase in the number of monocytes. In the future, it is planned to determine histological, histochemical and immunohistochemical changes in the organs of laboratory animals under the influence of plastic in a laboratory experiment. Завдяки своїй довговічності, універсальності та економічності вироби з пластику знайшли широке застосування у всіх сферах життя людини. Незважаючи на інертність полімерів, останні дослідження показують здатність мікропластику долати природні тканинні бар'єри, накопичуватися в організмі тварини, впливати на метаболізм і змінювати мікробіоту кишечника, негативно впливаючи на неї. У 42-денному експерименті встановлено зміни відносної маси внутрішніх органів, біохімічних і морфологічних показників крові білих мишей під впливом різних доз пінополістиролу в їх раціоні. Чотири групи білих мишей споживали подрібнені частинки пінополістиролу (10%, 1% та 0,1% від маси корму, контрольна група без додавання пінополістиролу). Наприкінці досліду визначали морфофункціональний стан внутрішніх органів за індексом маси органу та біохімічними показниками крові. Додавання до корму подрібненого пінополістиролу в кількості 1% викликає значне зниження індексу маси серця і шлунка, 10% – тільки серця, а 0,1% – не впливає на цей показник. Пінополістирол суттєво впливав на біохімічні показники крові незалежно від дози, викликаючи підвищення активності аспартатамінотрансферази на фоні зниження активності лужної фосфатази. Знижується вміст загального білірубіну, сечовини, азоту сечовини та холестерину, підвищується концентрація креатиніну та загального білка (за рахунок фракції альбуміну). Застосування подрібненого пінополістиролу у мишей не викликало істотних змін морфологічного складу крові, за винятком дозозалежного збільшення кількості моноцитів. Надалі планується в лабораторному досліді визначити гістологічні, гістохімічні та імуногістохімічні зміни в органах лабораторних тварин під впливом пластику.
Вплив пінополістиролу в різних дозах на показники крові та відносну масу внутрішніх органів білих мишей
Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X Лєщова Марина Олексіївна http://orcid.org/0000-0002-4251-4152
Keywords: blood enzymatic activity; ферментативна активність крові; microplastic; мікропластик; organ mass index; індекс маси органу; blood biochemical parameters; біохімічні показники крові; albumins; альбуміни; globulins; глобуліни